Vertical integration, separation and non-price discrimination: An empirical analysis of German electricity markets for residential customers - Vigen Nikogosian; Tobias Veith (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The literature on vertical integration in markets with regulated upstream prices suggests that the integrated upstream firm might engage in non-price discrimination. Several studies provide policy recommendations derived either from case study approaches or based on theoretical modeling which addresses the unbundling issue. In this study we analyze the impact of vertical integration of retail incumbent and network operator on retail prices and upstream charges. As the vertical structure is heterogeneous across the 850 German electricity submarkets for residential customers (there exist legally unbundled, vertically integrated or fully separated firms), we use firm level data to analyze the effects of different vertical structures and regulation schemes on retail electricity prices. We find significantly higher prices in markets with vertically integrated firms compared to markets with fully separated firms. This finding could indicate non-price discrimination. Furthermore, we find no evidence that legal unbundling eliminates the incentives for non-price discrimination because the prices do not differ from prices in markets under vertical integration.
Keywords: L1; L5; L9; 330; electricity; regulation; vertical integration; legal and total unbundling; non-price discrimination; Elektrizitätswirtschaft; Vertikale Konzentration; Preisdifferenzierung; Wohnimmobilien; Deutschland